Loaf slicer machine - Surani, Mohammad Syakir; Md Yusof, Muhammad Shalihin; Hassan, Mohd Fahrul; Md Junoh, Mohd Safa Ruddin; Hadison, Shahrul Azni; Mohamed Rilwan, Reehana (Penerbit UTHM, 2017)
Haji Makpol Bin Saimon is a founder of Kacang Pool Haji, the famous food in Johor Bahru. This food was inspired from Arabic dishes. The menu is prepared to meet the taste of Malaysian citizen especially Malays [1]. The delicious menu makes it famous among the people included VIPs and Singaporean. The ingredient used very simple and easy to dishes [2]. It is only uses “kacang parang” cooked with minced meat and mixed spices that is produced by Haji Makpol and after, prepared with Key Lime (limau purut), egg halved cooks and homemade bread. The bread that has been produced in a day is about 2400 pieces. This machine is gravity fed by the inclined delivery of bread through its blades into the receiving tray for bagging. Moreover, this machine is able to cut loaves bread into 8 pieces with thickness 3.75 cm per bread. There are no machines yet invented to meet the requirement of these breads. These breads are homemade especially for Kacang Pool Haji for his menus.